Arabic Writing Skill And Its Learning Problematics/ Keterampilan Menulis Bahasa Arab Dan Problematika Pembelajarannya - Hanun, Aisyatul; Mukminin, Amirul (Jurnal Bahasa Arab, 2024)
This study aims to determine the learning of Arabic writing skills (Maharah Kitabah) at MA Salafiyah Syafi'iyah Situbondo and its learning problems. MA Salafiyah Syafi'iyah is a madrasah diniyah with a local Islamic boarding school curriculum, whose students' backgrounds are from various levels of education; senior high school and college and even postgraduate. This study uses a descriptive qualitative research method approach. The instruments used in this study were observation through interviews with teachers, and students, and direct observation of the learning process of Arabic writing skills and the activity of writing Arabic articles. The results of the study in the third year, students were required to write Arabic articles in the form of mini research or essays. However, students still find it difficult to compile Arabic tarkib according to their qawa'id lughawiyah. Linguistic Problems; a) there are several errors: in writing tarkib isnadi, bayani and adadi, b) errors in giving harakat, c) errors in choosing diction or words (sentences) in making phrases (number of mufidah). Non-Linguistic Problems; a) no appropriate textbooks, b) monotonous learning methods, c) weak student attention and interest.